Flood Inundation Modeling Using Geomorphic Approaches, UAV, and GIS - Dhoni Wicaksono; Lufti Gita Iriani; Hendy Fatchurohman; Taufik Hery Purwanto; Dwi Setyo Aji; Warsini Handayani; Alfiatun Nur Khasanah (Politeknik Negeri Batam, 2020)
Flood is one of the most frequently occurring natural disasters in Indonesia. At the end of 2017, Tropical Cyclones Cempaka and Dahlia formed over the Indian Ocean, inducing extreme rains and floods in some parts of Java Island. The Special Region of Yogyakarta was among the most affected areas, especially along the Oyo River section in Imogiri District. This research was designed to identify and map the flood-prone areas in the district as part of flood mitigation measures. For this purpose, The Unmanned Aerial Vehicle (UAV) technology was used to not only provide a detailed and up-to-date description but also produce aerial photographs (orthoimages) and Digital Elevation Model (DEM). These two products were inputted to the inundation modeling developed with a geomorphic approach and simulated in a Geographic Information System (GIS). In terms of accuracy, the resulting models were quite reliable for mapping on a detailed scale and only slightly deviated from the traced inundation in the field. Also, five areas (sub-village) were found with the highest vulnerability to floods, namely, Trukan, Butuh, Dogongan, Siluk Satu, and Kedung Miri.